Melatonin-Mediated Abiotic Stress Tolerance in Plants - Zeng, Wen; Mostafa, Salma; Lu, Zhaogeng; Jin, Biao (Frontiers in Plant Science, 2022)
Melatonin is a multi-functional molecule that is ubiquitous in all living organisms. Melatonin performs essential roles in plant stress tolerance; its application can reduce the harmful effects of abiotic stresses. Plant melatonin biosynthesis, which usually occurs within chloroplasts, and its related metabolic pathways have been extensively characterized. Melatonin regulates plant stress responses by directly inhibiting the accumulation of reactive oxygen and nitrogen species, and by indirectly affecting stress response pathways. In this review, we summarize recent research concerning melatonin biosynthesis, metabolism, and antioxidation; we focus on melatonin-mediated tolerance to abiotic stresses including drought, waterlogging, salt, heat, cold, heavy metal toxicity, light and others. We also examine exogenous melatonin treatment in plants under abiotic stress. Finally, we discuss future perspectives in melatonin research and its applications in plants.